english English - Nur Syamsiyah; Misfi Laili Rohmi (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2021)
Islamic banks collect funds from the public and then send them for financing as an intermediary institution. In practice, the distribution of financing, which is the main characteristic of Islamic banks, is not as easy as the existing theory. This study will discuss the short-term and long-term effects of inflation, financing, and financing problems on deposit ratios in Indonesia's Islamic banking deposits. This study uses an Error Correction Model with monthly time series data starting from 2019-2020. The results show that all variables significantly affect deposits in Islamic banking in Indonesia in the long run. Meanwhile, in the short term, the inflation and financing variables significantly affect Islamic banking deposits in Indonesia, and the Financing to Deposit Ratio has no significant effect.